“Allure” as an Aesthetic Element in Novel - Shirzad Tayefi; Behzad Nazemianpour (مطالعات زبانی و بلاغی)
A novel is a linguistic art that engages sensory and intellectual-linguistic faculties at the same time. Since it is art, it promises us pleasure, and because it is rational, it maintains our relationship with its own internal logic and the logic of the outside world. Novel invites us, with its allure, to read and encourages us, with ongoing pleasure, to keep doing so. At a time when video-virtual narratives fascinate the world, novel can still hold the promise of unique pleasure beyond the reach of its competitors, fostering our focused reading. But, what kind of pleasure is this and what are the factors that induce pleasure in a novel? The question concerning its allure is a subset of aesthetic questions about novel. The allure of novel is at the core of its beauty, along with its truthfulness and irreducibility. In the Persian studies on novel, the allure and pleasure of reading novels has been less discussed. With an aesthetic and text-oriented approach, this research attempts to answer the question "How can a novel be alluring?". In the end, we will see that novel provides allure and aesthetic pleasure to the audience by stimulating curiosity, developing emotional experience, arousing passion, tension and the promise of a resolution, as well as detouring and postponement.